2009 34th IEEE Photovoltaic Specialists Conference (PVSC) 2009
DOI: 10.1109/pvsc.2009.5411365
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and implications of the boron rich layer resulting from open-tube liquid source BBR3 boron diffusion processes

Abstract: Boron diffusion is commonly associated with the formation of an undesirable boron rich layer (BRL), which is often made responsible for degradation of the carrier lifetime in the bulk. We therefore investigate the phenomenology of the BRL formation and its impact on sheet resistance and bulk lifetime. We use scanning electron microscopy (SEM) to investigate the thickness of the boron silicate glass (BSG) and the BRL. Additionally, we present sheet resistance measurements of diffused wafers and corresponding MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
(13 reference statements)
0
21
0
1
Order By: Relevance
“…It is reported that the opentube liquid source BBr 3 diffusion induces the crystal defects and the carrier lifetime degradation due to the formation of BRL at the surface [7,20]. On the contrary, it is also reported that the formation of BRL improves the lifetime owing to metallic impurity gettering of BRL [21].…”
Section: Carrier Lifetime After Boron Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the opentube liquid source BBr 3 diffusion induces the crystal defects and the carrier lifetime degradation due to the formation of BRL at the surface [7,20]. On the contrary, it is also reported that the formation of BRL improves the lifetime owing to metallic impurity gettering of BRL [21].…”
Section: Carrier Lifetime After Boron Diffusionmentioning
confidence: 99%
“…Thus, many boron diffusion processes have been proposed and used to fabricate the Ntype silicon solar cell. Open-tube liquid source diffusion of BBr 3 [7,8] must be a common industrial standard process but the number of process steps increases because of diffusion protection film formation on the opposite side. Ion implantation is the most advanced process and has precise controllability of the dopants [9].…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous phase diffusion of boron using hazardous BBr 3 or BCl 3 liquid source, that needs extra safety precautions, leading to the increase of the process cost [4]. Alternative B-dopant sources have also been investigated to lower the cost involved in B diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The minority carrier lifetime of passivated N-type silicon wafer can reached ms level [1][2]. At present, the two most commercialized solar cells, Panasonic HIT cells and Sun-power IBC cells with high photoelectric conversion efficiency are all based on N type silicon substrate [3][4].Therefore, the preparation process of N-type silicon-based solar cells has attracted widespread attention of researchers in recent years [5].…”
Section: Introductionmentioning
confidence: 99%